WOMAN AND RELIGION IN MODERN WESTERN CULTURE - Shermatova Malika (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Abstract. The social upheavals of the 20th century contributed to the fact that women were forced to expand the list of their traditional social roles, which could not but lead to a change in the status of women within religious organizations. The development of various women's movements, and in particular the feminist movement, has contributed to the growing interest of researchers in studying the role and images of women in religion.